DESAIN RISET MAQHASID SYARI’AH: UPAYA PEMBARUAN DALAM PENELITIAN - Muslihun Muslihun (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2019)
This study tries to describe the important position of maqhasid shari'ahas an alternative method in the scientific research design. Especially in the field of ijtihad maqhasidi, both using qualitative, quantitative, and mixed approaches. Based on the text analysis method, the results of the study show that the sharia maqhasidno longer only deals with the realm of the Qur'an and Sunnah texts, but can be used as a basis for contextual research in general. The work system of Islamic maqhasidresearch design is measured by the maintenance of the benefit of humans and their environment without the limit of space and time. So that, science can be directly proportional to the interests of humanity and the universe. As the universal vision of Islam, as a religion rahmatan lil 'alamiin. The research methods that usually well-known are only qualitative, quantitative, and mixed method, then the maqhasid shariamethod can be used as an alternative method, so that Islamic law can be always contextual. In other words, this method can be as s 'new' scientific research design model.